A nuclear-encoded endonuclease governs the paternal transmission of mitochondria in Cucumis plants - Jia Shen; Xiaolong Lyu; Xinyang Xu; Zheng Wang; Yuejian Zhang; Chenhao Wang; Eduardo D. Munaiz; Mingfang Zhang; Michael J. Havey; Weisong Shou (Nature Communications)
Abstract Non-Mendelian transmission of mitochondria has been well established across most eukaryotes, however the genetic mechanism that governs this uniparental inheritance remains unclear. Plants in the genus Cucumis, specifically melon and cucumber, exhibit paternal transmission of the mitochondrial (mt) DNA, making them excellent models for exploring the molecular mechanisms underlying mitochondrial transmission. Here, we develop a toolkit to screen for mutants in mitochondrial inheritance (mti), and use fine mapping to successfully identify a mitochondrially targeted endonuclease gene (MTI1) controlling mitochondrial transmission. Knockout of MTI1 results in a shift from paternal to bi-parental inheritance of the mtDNA, confirming the crucial role of MTI1 in uniparental inheritance of mitochondria. Moreover, we demonstrate that MTI1 exhibits robust endonuclease activity both in vitro and in vivo, specifically expresses in mitochondria of the fertilized ovule within 24 h of pollination. Collectively, this study reveals that a nuclear-encoded but mitochondria-targeted gene plays a causative role in governing the non-Mendelian mitochondrial inheritance, revolutionizing our knowledge about mitochondrial DNA transmission.